2007
DOI: 10.1152/ajpgi.00565.2006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a cannabinoid receptor agonist on colonic motor and sensory functions in humans: a randomized, placebo-controlled study

Abstract: Cannabinoid receptors (CBR) are located on cholinergic neurons in the brain stem, stomach, and colon. CBR stimulation inhibits motility in rodents. Effects in humans are unclear. Dronabinol (DRO), a nonselective CBR agonist, inhibits colonic motility and sensation. The aim of this study was to compare effects of DRO and placebo (PLA) on colonic motility and sensation in healthy volunteers. Fifty-two volunteers were randomly assigned (double-blind) to a single dose of 7.5 mg DRO or PLA postoperative with concea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
99
3
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(108 citation statements)
references
References 32 publications
3
99
3
3
Order By: Relevance
“…Nevertheless, there is not a clear correlation between compliance and pain perception (Käll et al, 2007;Lindström et al, 2008;Ravnefjord et al, 2008). Experimental data in humans showed that the nonselective cannabinoid dronabinol reduced colonic tone and increased compliance while increasing sensation ratings to distension, probably through the central modulation of perception (Esfandyari et al, 2007). In the present experiments, WIN55,212-2, at analgesic doses, did not modify the pressure-volume relationship during distension indicating a lack of effect modulating colonic compliance.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…Nevertheless, there is not a clear correlation between compliance and pain perception (Käll et al, 2007;Lindström et al, 2008;Ravnefjord et al, 2008). Experimental data in humans showed that the nonselective cannabinoid dronabinol reduced colonic tone and increased compliance while increasing sensation ratings to distension, probably through the central modulation of perception (Esfandyari et al, 2007). In the present experiments, WIN55,212-2, at analgesic doses, did not modify the pressure-volume relationship during distension indicating a lack of effect modulating colonic compliance.…”
Section: Discussioncontrasting
confidence: 67%
“…Recent studies in several species, including humans, support a role for endocannabinoids modulating visceral pain (Jaggar et al, 1998;Farquhar-Smith et al, 2002;Sanson et al, 2006;Esfandyari et (2006) implicated CB 1/2 Rs in the modulation of basal viscerosensitivity in rats. However, according to the present results, CB 1 Rs account for the full analgesic effects of cannabinoids on basal CRD-associated pain responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…45,46 VİSERAL DUYARLILIK CB'lerin viseral ağrı üzerine etkili olduğu birçok hayvan çalışmasında gösterilmiştir. CB1 ve CB2 reseptör agonistlerinin hem kolorektal distansiyon ile oluştu-rulmuş ağrı modelinde hem de inflamatuar uyaran ile oluşturulmuş viseral ağrı modelinde etkili olduğu gös-terilmiştir.…”
Section: Gastroi̇ntesti̇nal Moti̇li̇te üZeri̇ne Etki̇leri̇unclassified
“…46 Ancak bu hasta grubunda uyuşukluk, baş dönmesi ve sersemlik gibi yan etkilerin olması nedeni ile daha düşük dozlarda (2,5 ve 5 mg) ilacın kullanıl-dığı bir çalışmada, hastalarda tedavide fayda göz-lenmemiştir. 55 CB'lerin güçlü antiinflamatuar ve immünmo-dülator etkileri olması nedeni ile inflamatuar ve ağrı ile seyreden inflamatuar barsak hastalıkları (İBH)'nda etkin olabileceği düşünülmüştür.…”
Section: Kannabi̇noi̇dler Ve İnsan çAlişmalariunclassified